Pembuatan Buku Panduan Labor Komputer di Jurusan Bahasa dan Sastra Indonesia dan Daerah Fakultas Bahasa dan Seni Universitas Negeri Padang - Putri, Indah Kurnia; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractÂ It can be concluded the steps in making the Computer Labor Manual of the Indonesian Language and Literature Department and the Regional Language and Arts Faculty of the State University of Padang, as follows; (a) collecting data and information, (b) compiling the writing framework, (c) making front cover (d), (d) making introductory words, (e) making a table of contents, (f) making the main contents of the book, elements the main content contained in the computer labor manual of the Indonesian and regional languages and literature is to make chapter I discuss the introduction of computer labor profiles, containing a glimpse of computer labor, labor computer organizational structure, computer laboratory space layout, chapter II discusses service computer labor contains about computer labor service hours, computer laboratory rules, chapter III discusses information retrieval, contains computer labor management, procedures for borrowing computer labor facilities, and what applications are available on computers in Indonesian and regional language and literature majors, chapters IV makes a closing containing conclusions.Keywords: Computer Labor, Laboratory, Guidebook